A Vulnerable Flexibility: An Analysis of the Representation of Gig Workers' Sustainability in Indonesian Digital Media: Fleksibilitas yang Rentan: Analisis Representasi Keberlanjutan Pekerja Gig di Media Digital Indonesia - Murda, Muhammad; Febriyati, Tindia (Jurnal Ketenagakerjaan, 2025)
The digital transformation of Indonesia’s economy has generated a new labor ecosystem known as the gig economy, where online drivers, logistics couriers, and digital freelancers perform flexible yet precarious work through algorithmic platforms. While this model offers autonomy and efficiency, it simultaneously produces new forms of dependency, income instability, and the erosion of social protection. Beyond its economic dimension, the gig economy also signifies a profound cultural shift in how work, identity, and value are constructed in the digital era. This study examines how the sustainability of gig workers’ livelihoods is represented within Indonesia’s digital media landscape, focusing on tensions between dominant narratives of digital competitiveness and counter-narratives of injustice, exhaustion, and collective resistance. Employing a qualitative Critical Discourse Analysis (CDA) using Fairclough’s three-dimensional framework—textual, discursive, and socio-political—this research analyzes online news, social media posts, and protest videos published between 2023 and 2025. The findings reveal that public narratives frequently glorify flexibility as a symbol of progress while obscuring the structural and cultural vulnerabilities faced by gig workers. Conversely, worker-generated counter-narratives articulate cultural solidarity and digital resistance against algorithmic exploitation. By situating the gig economy within Indonesia’s socio-cultural context, this study argues that the sustainability of digital labor requires not only economic inclusion but also cultural recognition and decolonial understandings of work, identity, and justice. Therefore, policy reforms should integrate workers’ lived experiences, media narratives, and cultural meanings to ensure a fair and sustainable digital transformation.